Improving Speed Reading Ability Using the Speed Reading Method in Class V SDIT Hamas Stabat - Pradana Chairy Azhar; Azri Ranuwaldy Sugma (Budapest International Research and Critics University, 2022)
This research is classroom action research with the aim of improving students' speed-reading skills. This research is conducted at SDIT Hamas Stabat. The subjects of this study were 20 students of class V SDIT and the object of this research was to improve speed reading skills by using the speed-reading method. This study uses tests, reflections and documentation. The assessment indicator in speed reading is 75 wpm and the success achieved by students is at least 75% of students can read quickly. In the initial test only 4 people who have the ability to read quickly with a percentage of 20% and who do not yet have the ability to read quickly as many as 16 people with a percentage of 80%. In the first cycle there were 11 students who were able to read quickly with a percentage of 55% and those who were still not able to read quickly were 9 students with a percentage of 45%. In the second cycle there was a significant increase with many 17 students who had the ability to read quickly with a percentage of 85% and who had not been able to read quickly as many as 3 people with a percentage of 15%. The speed-reading method can be used by teachers to improve speed reading skills.